FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA BIDAN DALAM PENDOKUMENTASIAN BUKU KIA - Heni Suryani; Joko Sapto Pramono; Nursari Abdul Syukur; Bety Mure (MMJ (Mahakam Midwifery Journal), 2020)
Abstract MCH is a proof of the overall and continuous recording maternal and child health services held by the mother. This type of research is descriptive cross sectional design. The population was all 20 midwives at Muara Badak Health Center, the sample was the total population. The instruments used in the study were questionnaires and observations. Data analysis used the chi-square test. Characteristics of midwives were mostly aged 20-30 years 55%, last education completed D3 95% and years of service 1-10 years 80%. Good knowledge 65%, positive attitude 75%, good skills 75%, good motivation 65%, compensation system is good 70%, workload is good 85%, work climate is good 55% and midwife performance is good 70%. There is an influence of knowledge (p value: 0.007), attitude (p value: 0,000), skills (p value: 0.014), motivation (p value: 0.007) and workload (p value: 0.018) on the performance of midwives in the MCH Book documentation. However, there was no effect of the compensation system (p value: 0.613) and work climate (p value: 0.119) on the performance of midwives in the documentation of the MCH Handbook. Factors that affect midwives performance in documenting MCH book was knowledge, attitudes, skills, motivation and workload. Keywords: Performance, Midwife, Documentation, MCH Handbook. Abstrak Buku Kesehatan Ibu dan Anak (KIA) merupakan alat bukti pencatatan pelayanan kesehatan ibu dan anak secara menyeluruh dan berkesinambungan yang dipegang oleh ibu atau keluarga. Jenis penelitian deskriptif desain cross sectional. Populasi adalah seluruh bidan di Puskesmas Muara Badak berjumlah 20 orang, sampel adalah total populasi. Instrumen yang digunakan dalam penelitian adalah kuesioner dan observasi. Analisa data menggunakan uji chi-square. Karakteristik bidan sebagian besar umur 20-30 tahun 55%, pendidikan terakhir tamat D3 95% dan masa kerja 1-10 tahun 80%. Pengetahuan baik 65%, sikap positif 75%, keterampilan baik 75%, motivasi baik 65%, sistem kompensasi baik 70%, beban kerja baik 85%, iklim kerja baik 55% dan kinerja bidan baik 70%. Ada pengaruh pengetahuan (p value : 0,007), sikap (p value : 0,000), keterampilan (p value : 0,014), motivasi (p value : 0,007) dan beban kerja (p value : 0,018) terhadap kinerja bidan dalam pendokumentasian Buku KIA. Namun tidak ada pengaruh sistem kompensasi (p value : 0,613) dan iklim kerja (p value : 0,119) terhadap kinerja bidan dalam pendokumentasian Buku KIA. Kata Kunci : Kinerja, Bidan, Pendokumentasian, Buku KIA.